IMPLEMENTASI GAYA MENGAJAR YANG MENARIK GUNA MENINGKATKAN MINAT BELAJAR SANTRI PADA YAYASAN HUDATUL FALLAH CISEENG KABUPATEN BOGOR - Irfan Rizka Akbar; Mitri Nelsi; Lily Setyawati Kristianti (Abdi Jurnal Publikasi, 2022)
The purpose of Community Service activities is to carry out one of the tri dharma of higher education. In addition, it is hoped that with community service the existence of higher education can make a major contribution to the development and application of science to society. The method used in this community service is in the form of counseling and coaching, namely in addition to actions, processes and results or better statements. In this case it shows progress, increased growth, evolution of various possibilities, development or improvement of something. The result of community service that is obtained is an increase in knowledge regarding the implementation of an interesting teaching style in order to increase the demand for learning from students so that it becomes what they want in learning and teaching activities. And hope to have an extraordinary impact on the surrounding community. Keywords: Teaching Style